New occurrence of B chromosomes in Partamona helleri (Friese, 1900) (Hymenoptera, Meliponini) - Cinthia Caroline Cardoso Martins (Genetics and Molecular Biology, 2009)
Cytogenetic analyses of the stingless bee Partamona helleri collected in the state of Bahia, Northeast Brazil revealed the chromosome numbers n = 18 in the haploid males and 2n = 35 in the diploid females. All karyotypes displayed one large acrocentric B chromosome, which differs from the minute B chromosomes previously described in the populations from southeastern Brazil. Giemsa staining, C-banding and DAPI/CMA3 fluorochrome staining also revealed a remarkable interpopulational divergence regarding both the regular karyotype and the B chromosomes. The B chromosomes found in the samples from Jequié, Bahia, were entirely heterochromatic, while those found in Cravolândia, Bahia, displayed a euchromatic portion at the telomeric end of the long arm. CMA3 labeling sites varied from seven to eight between the two localities in Bahia, due to the presence of an extra GC-rich block in the karyotype of the samples from Jequié. This is the first report of a large B chromosome in P. helleri and reveals the occurrence of a geographic differentiation within this species.